Poetics - S. N. Nyeck (African Journal of Gender and Religion (AJGR))
Audre Lorde is a household name within Black queer communities and has almost exclusively been associated with scholarship on gender and sexuality. Her early political involvement in Africa’s liberation in the context of Négritude, a pan-African movement of self-affirmation, has largely gone unnoticed, inad- vertently giving credence to the unfounded but popular idea that queer folk s are not interested in Africa’s political priorities. This essay is written with the view that Africa and her Diaspora need preeminent queer actors influencing the present and future trajectories and strategies to be considered in defence of a Black dignified presence in the world and against global racism. It is further submitted that the personal is not just political – it is primarily spiritual. Hence the triad, personal, spiritual, and political has implications for our appraisal of meanings within the Africana household. The  exploration  of poetry as a spiritual practice of the queered self in this essay blurs the boun- daries between religion and politics in order to offer an integral account of gender diversity within the Africana household. We need to collectively learn from the experiences that not just resist racial oppression but also from those that simultaneously free the heart. From this vantage point, Audre Lorde’s poetics is read as internal recommendations for building up the Africana dwelling by calling out what remains dormant or imperfectly considered within the realm of spiritual and political imagination: queer recesses of the heart.